'A Triumph of the Rich': Tractarians and the Reformation. Issue 1 (1st April 2014) - Skinner, Simon
Abstract: That hostility to the Reformation was a feature of the Oxford Movement's outlook is a truism, but Tractarians' anti-Reformation sentiments went much further than the purely theological. Tractarians consistently held that in its repudiation of antiquity and elevation of sola scriptura, the Reformation had launched a wider rationalism whose socio-economic as well as religious consequences they abhorred. If a Tractarian paternalism - which mourned the welfare consequences of the dissolution of the monasteries, and the rise of capitalism and its bourgeoisie - had much in common with other nineteenth-century social criticism, a crucial difference emerged at the point of prescription. Their uncompromising advocacy of the church as the sole agency of amelioration, and promotion of such schemes as sisterhoods, sharply distinguished Tractarians from advocates of legislative intervention or ethical socialism. Tractarians therefore looked not forward, to the ideal of a welfare state, but back, to the ideal of a welfare church.